THE ROLE OF MARKETING IN IMPROVING THE SYSTEM OF AGRICULTURAL PRODUCTION - Musayeva Shoira Azimovna; Usmanov Farzod Shokhrukhovich (International Journal of Human Computing Studies, 2020)
This article is devoted to the development of marketing services in agriculture, in particular to the production of fruits and vegetables. The features of marketing in the activities of exporters of agricultural products are shown.